Sle With Antiphoslipid Antibody Syndrome And Autoimmune Hemolytic Anaemia Presenting Cerebral Venous Sinus Thrombosis - A Rare Combination - Rahman, Aminur; Twinkle, Furial Quraishi; Hakim, Khondker Mahmudul; Shapnil, Ahammed Ali; Arko, Hamimur Rahman; Motin, Jemima; Quraishi, Firoz Ahmed (Bangladesh Journal of Medicine, 2022)
The combination of Antiphospholipid Antibody Syndrome (APS) and Autoimmune Haemolytic Anemia (AIHA) is extremely unusual. However, APS with underlying SLE has a well-documented link to Coomb’s positive AIHA. Antiphospholipid antibody syndrome and autoimmune haemolytic anaemia can cause cerebral venous sinus thrombosis, which is a rare neurologic symptom. We reported a 16- year-old girl reported to the neurology ward with a dull aching headache in the occipital region, as well as a fever. MRI and MRV of brain was done and showed thrombosis in the posterior half of superior sagittal sinus, right transverse, sigmoid and straight sinus. Anti-Ds DNA, ANA, and direct and indirect Coomb’s tests were all positive. Anti-Cardolipin IgM levels were high, and lupus anticoagulants (LA1 and LA2) were positive. The importance of recognizing an uncommon presentation of SLE with antiphospholipid syndrome and autoimmune haemolytic anemia (AIHA) with cerebral venous sinus thrombosis is highlighted in this case report. Bangladesh J Medicine 2022; 33: 220-223